EMERGENCE OF AI-DRIVEN INFLUENCERS: ANALYZING THEIR EFFECTS, ETHICAL ISSUES, AND STRATEGIC VALUE IN BRAND MARKETING - Muh Syulhasbiullah; Harmina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Artificial Intelligence (AI)-driven influencers have emerged as a transformative innovation in digital marketing, reshaping how brands engage with consumers through personalized, scalable, and data-driven communication. This study aims to analyze the effects of AI-driven influencers on consumer engagement and brand marketing, examine the ethical issues associated with their implementation, and evaluate their strategic value in contemporary marketing practices. The research employs a systematic literature review (SLR) approach following the PRISMA framework. Relevant studies published between 2020 and 2025 were collected from the Scopus database and analyzed using thematic synthesis and bibliometric mapping with VOSviewer. The review included 30 peer-reviewed articles that met the predefined inclusion criteria. The findings indicate that AI-driven influencers significantly enhance consumer engagement, improve brand communication, and enable highly personalized marketing strategies through advanced artificial intelligence technologies. However, the widespread adoption of AI influencers also raises critical ethical concerns, including transparency, authenticity, algorithmic bias, and data privacy, which require appropriate governance and regulatory frameworks. Bibliometric analysis further reveals that research on AI influencers has increasingly shifted toward issues of consumer trust, ethical AI deployment, and strategic brand communication. The study concludes that AI-driven influencers represent a valuable strategic asset for modern brand marketing when supported by responsible AI governance, transparent communication, and consumer-centered marketing practices. These findings provide practical implications for marketers and contribute to the growing body of knowledge on AI-enabled digital marketing.